2015
DOI: 10.1055/s-0035-1564055
|View full text |Cite
|
Sign up to set email alerts
|

Using the Endoscopic Endonasal Transclival Approach to Access Aneurysms Arising from AICA, PICA, and Vertebral Artery: An Anatomical Study

Abstract: Objective?To explore the use of the endoscopic endonasal transclival approach (EEA) for clipping anterior inferior cerebellar artery (AICA), posterior inferior cerebellar artery (PICA), and vertebral artery (VA) aneurysms. Design?Anatomical study. Participants?Fifteen adult cadavers. Main Outcome Measures?Length of artery exposed and distance from the nasal ala to the arteries. Results?The length of the right and left VA exposed were 1.7???0.6 cm and 1.6???0.6 cm, respectively. The distance to the right VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…There are also some literature reports on the cadaver study using the EEA for clipping intracranial aneurysms. [30][31][32][33][34][35][36][37][38][39][40][41] Many previous articles on cadaver studies have suggested that ACoA aneurysms can be clipped through the EEA, but Montaser et al 32 did not fully agree. To further analyze the clipping of ACoA aneurysms by this approach, we first simulated the approach with a cadaver head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also some literature reports on the cadaver study using the EEA for clipping intracranial aneurysms. [30][31][32][33][34][35][36][37][38][39][40][41] Many previous articles on cadaver studies have suggested that ACoA aneurysms can be clipped through the EEA, but Montaser et al 32 did not fully agree. To further analyze the clipping of ACoA aneurysms by this approach, we first simulated the approach with a cadaver head.…”
Section: Discussionmentioning
confidence: 99%
“…In general, there are not many cases, only 29, and in these limited cases, ACoA aneurysm is not a high proportion. There are also some literature reports on the cadaver study using the EEA for clipping intracranial aneurysms 30–41 . Many previous articles on cadaver studies have suggested that ACoA aneurysms can be clipped through the EEA, but Montaser et al 32 did not fully agree.…”
Section: Discussionmentioning
confidence: 99%
“…26,43 Special endonasal instruments should be designed and used for endoscopic aneurysm surgery. 8,41 Finally, the surgeon should have extensive experience with the EEA before attempting to treat a cerebral aneurysm with this technique. 19,27,40…”
Section: Discussionmentioning
confidence: 99%
“…10,12,13,19,27,41 However, these studies, as well as the few available anatomical studies, have mainly focused on the feasibility of endoscopic surgical access to this region, failing to provide relevant surgical anatomical details and objective evidence on the extent of vascular control over vessels in the BAX region during an EEA. 4,7,8,34,42 Furthermore, no study has compared the EEA with any of the common transcranial approaches to the BAX to provide a clear profile of the relative advantages and limitations of the EEA for treating BAX aneurysms.…”
mentioning
confidence: 99%
“…Endoscopic endonasal approaches have evolved through the years, from the resection of pituitary and transsellar lesions with extension posteriorly to the posterior clinoid and foramen magnum, to the resection of more complex lesions in close proximity to the internal carotid artery (ICA) and/or adjacent neural and vascular structures . Expanded endoscopic approaches have also advanced with the development of new techniques to include medial approaches to the orbit.…”
mentioning
confidence: 99%